2014
DOI: 10.1152/ajpendo.00597.2012
|View full text |Cite
|
Sign up to set email alerts
|

Loss of HIF-1α impairs GLUT4 translocation and glucose uptake by the skeletal muscle cells

Abstract: Abiko A, Haneda M. Loss of HIF-1␣ impairs GLUT4 translocation and glucose uptake by the skeletal muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 29 publications
(29 reference statements)
4
42
0
1
Order By: Relevance
“…It should be noted that addition of the vehicle control (DMSO) in the inhibitor studies yielded alterations in the relative amounts of glucose uptake when compared to non-DMSO treated cells (Figure 1A). STAT3 has previously been shown to mediate glucose up through HIF1α induced translocation of GLUT4 (Demaria et al, 2010; Sakagami et al, 2014). Indeed IL-15 induced an increase in mRNA expression levels of HIF1α and these effects were prevented with STAT3 inhibition in the presence of IL-15 ( P < 0.05; Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that addition of the vehicle control (DMSO) in the inhibitor studies yielded alterations in the relative amounts of glucose uptake when compared to non-DMSO treated cells (Figure 1A). STAT3 has previously been shown to mediate glucose up through HIF1α induced translocation of GLUT4 (Demaria et al, 2010; Sakagami et al, 2014). Indeed IL-15 induced an increase in mRNA expression levels of HIF1α and these effects were prevented with STAT3 inhibition in the presence of IL-15 ( P < 0.05; Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…We explored a potential role for these transcription factors in arsenite-induced glycolysis and found that only HIF-1α was required for arsenite-induced glycolysis. In skeletal muscle cells, translocation of Glut-4 from intracellular vesicles to the plasma membrane is a necessary step for glycolysis [12]. Indeed, accumulation of Glut-4 in the plasma membrane fraction of the L-02 cells was increased by their exposure to arsenite; this effect was blocked by HIF-1α knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…HIFs are sensitive to environmental factors, especially arsenite, and, under normoxic conditions, they are involved in the regulation of a variety of cellular functions and thereby contribute to various malignancies [8,9]. HIF-α binds to hypoxia response elements (HREs) of target genes for vascular endothelial growth factor [10], glycolytic enzymes [11], and glucose transporters [12,13], which are related to aspects of cancer growth, including proliferation, angiogenesis, and glycolysis. HIF-α expression is also increased, however, under certain normoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we speculated that intrinsic ACh synthesized by ChAT-expressing cells also may have a role similar to that of extrinsic ACh. HIF-1α is a master transcription factor responsible for glucose metabolism, including glycolysis and glucose uptake and utilization [9,10,11]. Thus, increased ACh levels in ChAT-expressing cells may have a crucial role in upregulating the HIF-1α protein level and promote cells to use glucose more efficiently.…”
Section: Discussionmentioning
confidence: 99%